Interleukin 13 (Il-13) Acts As A Profibrotic Cytokine For Recruitment Of Myofibroblasts In Oral Submucous Fibrosis (Applied Biological Research, 2019)
Oral submucous fibrosis (OSF) is a chronic inflammatory condition due to  areca nut (Areca catechu) chewing which induces fibrosis leading to the  difficulty in mouth opening. Various profibrotic cytokines and chemokines  have been found involved in fibrosis. The present study was aimed to find the  role of interleukin 13 (IL-13) in recruiting the myofibroblasts and as a  causative factor for fibrosis in OSF. Twenty-five sections of OSF tissue and  ten sections of normal mucosa were stained with IL-13, TGF-β1 and α-SMA  antibodies using immunohistochemical method. Immunostaining was done to  assess staining intensity and percentage of positive cells. The results were  analyzed by SPSS software. The expression of all three markers IL-13, TGF β1 and α-SMA showed significant difference between control and OSF (p
Keywords: Interleukin 13; myofibroblasts; oral submucous fibrosis; pathogenesis; transforming growth factor-β